LONGSTANDING, REPETITIVELY MISDIAGNOSED KYRLE’S DISEASE IN A PATIENT WITH END-STAGE RENAL DISEASE: A CASE REPORT - Dohcheva Karajovanov, Ivana; Nikolovska, Suzana; Gocev, Gjorgji; Dimova, Maja; Mitrova Telenta, Julija; Dohchev, Sasho (University Ss. Cyril and Methodius in Skopje, 2023)
Kyrle’s disease (KD) is a rare variant of acquired perforating dermatosis (APD), associated with systemic diseases in adults, particularly chronic kidney disease (CKD) and diabetes mellitus (DM). Hyperkeratotic papules of KD are clinically important as a sign of a systemic disorder that are often misdiagnosed, so clinicopathological correlation is needed to establish the diagnosis. We report a rare case with longstanding KD, associated with end-stage renal disease (ESRD) on hemodialysis for 25 years that was repetitively misdiagnosed as folliculitis, excoriations and prurigo nodularis. The KD skin changes started to develop during earlier stages of CKD, before the kidney disease was suspected, and continued to appear in flares with extensive lesions when the systemic disease in the background was not under control. Dermoscopy revealed a 3-zonal concentric pattern, characterized by bright whitish scales in the centre, a structureless whitish-grey area surrounding the central crusts, and a peripheral, rose/brown pigmentation. Histopathological examination revealed moderately acantathotic epidermal invagination filled with a keratotic plug admixed with cellular debris and neutrophils, and a modest parakeratosis. Our goal is to emphasize that the accurate and timely diagnosis is vital to be able to monitor patients for a life threating, systemic disease such as kidney failure, and attaining better management of the dermatological status which can become longstanding and hindering, as well as to outline the importance of the multidisciplinary approach to improve outcomes in patients affected by KD.
Keywords: Kyrle’s disease, acquired perforating dermatosis, chronic kidney disease, end-stage renal disease, hemodialysis